Five accessibility challenges in access auditing mosque designs - Abd Samad, Nur Amirah; Abdul Rahim, Asiah; Said, Ismail (AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Mala, 2019)
Mosques are frequently visited because it is a place for worshipping God for devoted Muslims and its communal qualities. The lack of accessibility creates physical barriers for PwDs and the elderly and has discouraged them from joining congregational prayers. Mosque accessibility is a prolonged issue that needs mitigation hence the access challenges. Five accessibility challenges are discussed by assessing the Mosque's typical design and its facilities to its level of accessibility. Conclusively, the five access challenges reviewed in Access Auditing of mosque’s cases should be the focus for renovation and upgrading to be an inclusive Mosque.